Simple Finite Jordan Pseudoalgebras - Kolesnikov, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We consider the structure of Jordan H-pseudoalgebras which are linearly finitely generated over a Hopf algebra H. There are two cases under consideration: H = U(h) and H = U(h) # C[Γ], where h is a finite-dimensional Lie algebra over C, Γ is an arbitrary group acting on U(h) by automorphisms. We construct an analogue of the Tits-Kantor-Koecher construction for finite Jordan pseudoalgebras and describe all simple ones.